On a growing central banks accountability for financial stability – macroprudential perspective - Matysek-Jędrych, Anna (Economics and Business Review, 2018)
The aim of this paper is to identify and assess, on a comparative, intra-country basis, the existing practices and developments in central bank accountability for financial stability, from a new–macroprudential policy–perspective. The paper aims to contribute to the ongoing debate on institutional arrangements for macroprudential policy. The debate as to whether the combination of monetary policy and financial supervision within one institution is not new. Nevertheless it is far from being resolved. The paper points to the need to establish clear, formal and robust mechanisms of central bank involvement in the process of executing macroprudential policy, at least as a data collection and analyzing institution.